The Ease of Investing in Indonesia's Capital Market Based on Improved Financial Literacy, Investment Community and Capital Market School - Moh. Fathur Rozi; Jeni Susyanti; Ety Saraswati (Inovbiz: Jurnal Inovasi Bisnis, 2021)
Indonesia is predicted to have the 4th largest GDP in the world by 2050. One of the major contributors to GDP is investment. Based on KSEI data (2020) the number of investors in Indonesia is still 3.27 million investors or 1.73% of the total productive age population. This proves that Indonesia still needs encouragement to become the country with the 4th largest GDP in the world. One form of this encouragement is to increase people's financial literacy. Data from OJK (2019) states that the financial literacy index of the Indonesian people rose from 29.7% in 2016 to 38.03% in 2019. The investment community is one of the drivers and the ISP community is one of the capital market education activists. The importance of improving financial literacy, the investment community and capital market schools for the ease of investing is an important point to help make Indonesia a country with the 4th largest GDP in the world. The purpose of this study was to determine whether there is an influence between financial literacy, investment community and capital market schools on the ease of investing. The method that used is quantitative with a survey approach. The results show that there is an influence between financial literacy, the investment community and the capital market on the ease of investing, which means that if there is an increase in financial literacy, the investment community and capital market schools, there will also be an increase in the ease of investing.